Effects of EDTANa2Fe on phytoavailability of cadmium and arsenic to rice (Oryza sativa L.) - Xinhui Zhang; Hong Shuai; Chao Xu; Zhongyuan Wang; Shen Zheng; Hanhua Zhu; Daoyou Huang; Quan Zhang; Qihong Zhu (Ecotoxicology and Environmental Safety, 2024)
Cadmium (Cd) and arsenic (As) that accumulate in rice grains can enter the human body via ingestion, posing a human health threat. Chelated iron (Fe) fertilizer application is an effective strategy for reducing Cd and As concentrations in grains; however, its mechanism of action is unknown. We investigated effects of ethylenediamine tetraacetic acid disodium ferrous (EDTA·Na2Fe) at Fe application rates of 0, 25, 50, and 75 mg kg−1 on Cd and As availability in soil and accumulation in rice grains. EDTA·Na2Fe significantly reduced soil CdAs availability and significantly decreased CaCl2Cd and KH2PO4As concentrations by 27.8–39.2 % and 17.7–28.4 %, respectively. EDTA·Na2Fe facilitated Fe plaque (IP) formation and increased Cd (CdIP) and As (AsIP) sequestration in IP; furthermore, FeIP, CdIP, and AsIP increased significantly by 70.7–125 %, 109–150 %, and 88.1–168 %, respectively. In roots, EDTA·Na2Fe reduced the Cd concentration (CdR) but increased the As concentration (AsR). EDTA·Na2Fe reduced the Cd (CdG) and As (AsG) concentrations in grains by 29.8–46.2 % and 18.5–33.3 %, respectively. The optimal simultaneous reduction effect of CdG and AsG was observed at an EDTA·Na2Fe application rate of 50 mg kg−1 Fe. The results indicated that CdG was mainly affected by Cd availability, translocation factor (TF) CdR/CdIP, and TF CdG/CdR, and AsG was mainly affected by TF AsG/AsR, followed by TF AsR/AsIP and AsIP. In summary, EDTA·Na2Fe reduced CdG and AsG by reducing Cd and As availability in soil, improving Cd and As sequestration in IP, and reducing Cd transport from IP to roots and As transport from roots to grain. Moderate application of EDTA·Na2Fe effectively reduced CdG and AsG in CdAs-contaminated paddy soil.